Effects of Illness Management and Recovery: A Multicenter Randomized Controlled Trial - Roosenschoon, Bert-Jan; van Weeghel, Jaap; Deen, Mathijs L.; van Esveld, Emmie W.; Kamperman, Astrid M.; Mulder, Cornelis L. (Frontiers in Psychiatry, 2021)
There have been inconsistent findings in the literature with respect to the efficacy of Illness Management and Recovery (IMR) in the psychosocial treatment of people with schizophrenia or other severe mental illnesses. This study aimed to comprehensively investigate the effectiveness of IMR, including the impact of completion and fidelity. In this randomized controlled trial (RCT), 187 outpatients received either IMR plus care as usual (CAU) or only CAU. Multilevel modeling was implemented to investigate group differences over an 18-month period, comprising 12 months of treatment and six months of follow-up. The primary outcome was overall illness management, which was assessed using the client version of the IMR scale. Secondary outcomes included measures regarding illness management, clinical, personal, and functional recovery, and hospitalizations. The interviewers were blinded to group allocation. This clinical trial was registered with the Netherlands Trial Register (NL4931, NTR5033). Patients who received IMR showed statistically significant improvement in self-reported overall illness management (the primary outcome). Moreover, they showed an improvement in self-esteem, which is a component of personal recovery. There were no effects within the other questionnaires. There were also no statistically significant between-group differences in terms of hospitalizations. Patients in both groups showed statistically significant improvement in clinician-rated overall illness management, social support, clinical and functional recovery, and self-stigma over time. IMR completion was associated with stronger effects. High IMR fidelity was associated with self-esteem. This study confirms the efficacy of IMR in overall illness self-management. To our knowledge, this is the first RCT on IMR to explore the impact of fidelity on treatment efficacy. Future studies should further establish efficacy in personal recovery. To improve efficacy, it appears important to promote IMR completion and fidelity.